2003
DOI: 10.1161/01.atv.0000074878.29805.d0
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Deficiency Attenuates Atherosclerosis in Female Apolipoprotein E–Deficient Mice

Abstract: Objective-Osteopontin (OPN), a noncollagenous adhesive protein, is implicated in atherosclerosis, in which macrophages within atherosclerotic plaques express OPN. However, it is not known whether the elevated OPN expression is a cause or result of atherosclerosis. Methods and Results-We generated mice that lacked OPN and crossed them with apolipoprotein (apo) E-deficient mice and analyzed these mice with a mixed C57BL/6ϫ129 background after 36 weeks on a normal chow diet. In female mice, OP ϩ/Ϫ E Ϫ/Ϫ and OP Ϫ/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
141
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(152 citation statements)
references
References 37 publications
5
141
3
3
Order By: Relevance
“…27 In addition, it was reported that in OPN-defective mice, fibrosis and arteriosclerotic changes were attenuated. 28,29 In this study, OPN gene transcription activity was enhanced dose-dependently and timedependently in Aldo-stimulated rVSMCs, which is consistent with reports in other various cell species, such as renal mesangium cells, 19 renal fibroblasts 21 and vascular endothelial cells. 30 As the basal levels of Aldo in the plasma of humans are around 3Â10 À10 M, a significant increase in OPN transcription starting at a concentration of 10 À9 M, as was observed in this in vitro analysis, seems to be within the clinical plasma Aldo fluctuation range.…”
Section: Discussionsupporting
confidence: 91%
“…27 In addition, it was reported that in OPN-defective mice, fibrosis and arteriosclerotic changes were attenuated. 28,29 In this study, OPN gene transcription activity was enhanced dose-dependently and timedependently in Aldo-stimulated rVSMCs, which is consistent with reports in other various cell species, such as renal mesangium cells, 19 renal fibroblasts 21 and vascular endothelial cells. 30 As the basal levels of Aldo in the plasma of humans are around 3Â10 À10 M, a significant increase in OPN transcription starting at a concentration of 10 À9 M, as was observed in this in vitro analysis, seems to be within the clinical plasma Aldo fluctuation range.…”
Section: Discussionsupporting
confidence: 91%
“…In turn, the lower amounts of osteopontin may have adversely affected collagen deposition or reduced plaque growth by decreasing macrophage infiltration. 22 Paradoxically, collagen content was increased in the absence of MMP-9 after mouse carotid ligation. 23 We speculate that these apparently discrepant results may be related to model differences, more specifically to the absence (the former study) or presence (our study) of macrophages, which have been documented to induce SMCs to switch to a synthetic phenotype in an MMP-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, valsartan attenuated OPN expression and neointimal formation in the balloon-injured rat carotid artery. Accumulating evidence suggest that OPN plays an important role in the development of atherosclerosis (9,11). Importantly, OPN disruption has been shown to attenuate Ang II-accelerated atherosclerosis and aneurysm formation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that OPN promotes migration, extracellular matrix invasion, and proliferation of VSMC (5,7). Furthermore, OPN transgenic mice show exaggerated atherosclerosis and neointimal formation (8,9), while OPN deficiency attenuates atherosclerosis (10,11). These findings indicate that OPN plays an important role in the development of atherosclerosis and restenosis after coronary intervention.…”
mentioning
confidence: 97%